2018
DOI: 10.1007/s00436-017-5743-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein profiling of Acanthamoeba species using MALDI-TOF MS for specific identification of Acanthamoeba genotype

Abstract: Acanthamoeba spp. are ubiquitous in the environment and have the potential to cause severe infections. The different genotypes of Acanthamoeba have been shown to influence the severity of the disease and response to therapy. Characterizing Acanthamoeba spp. upto genotype can aid in infection control practices. Twenty-five Acanthamoeba isolates, characterized by 18S rDNA sequencing, were subjected to MALDI-TOF MS analysis by creating a database for the individual genotypes. The differentiating features of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…In addition, according to Cooper et al [26], the animal call rate was also related to genotyping accuracy, the individual call rate ranged from 96-99% in our study. All the above results demonstrated that the genotyping data got in the present study was validated, and the method of MALDI-TOF MS could be a stable platform for genotyping those SNPs [27,28].…”
Section: Resultssupporting
confidence: 63%
“…In addition, according to Cooper et al [26], the animal call rate was also related to genotyping accuracy, the individual call rate ranged from 96-99% in our study. All the above results demonstrated that the genotyping data got in the present study was validated, and the method of MALDI-TOF MS could be a stable platform for genotyping those SNPs [27,28].…”
Section: Resultssupporting
confidence: 63%
“…In addition, according to Cooper et al [21], the call rate of the animal was also related to genotyping accuracy, the individual call rate ranged from 96-99% in our study. All the above results revealed that the genotyping data got in the present study was validated, and the method of MALDI-TOF MS could be a stable platform for genotyping those SNPs [22,23].…”
Section: Discussionsupporting
confidence: 62%
“…A second recent alternative method for the rapid identification of isolates is MALDI-TOF MS, a mass spectrometry technology used for rapid, automated and, hopefully, accurate microbial phenotypic identification. This technology has been used in two small studies to correctly assign Acanthamoeba strains into appropriate sequence types [ 116 , 117 ]. Whether the use of MALDI-TOF MS expands in the analysis of Acanthamoeba remains to be seen.…”
Section: What Additional Approaches Are Available?mentioning
confidence: 99%